Investigation of efficiency and safety in wireless capacitive power transfer through a single-layer tissue phantom - Yusmarnita Yusop; Amy Sarah Ngu; Cheok Yan Qi; N. B. Asan; Huzaimah Husin; Shakir Saat; Peter Adam Hoeher (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Wireless power transfer (WPT) is a promising solution for implantable biomedical devices, offering an alternative to traditional implanted batteries and percutaneous connections, which are limited by short lifespans and high infection risks. Existing capacitive power transfer (CPT) systems for biomedical implants often utilize media such as animal meat or liquids to validate power transfer across the human body, but these materials exhibit inconsistent and inaccurate dielectric properties. To address this limitation, this study proposes a CPT system designed to operate with a single-layer tissue phantom that closely mimics the dielectric characteristics of human tissue. The system is integrated with a class-E LCCL resonant topology to enhance power transfer efficiency. In addition to evaluating performance, this work also investigates safety aspects in terms of electric field emission and specific absorption rate (SAR). Simulations using MATLAB Simulink and ANSYS HFSS reveal that at a 1 mm tissue gap, the electric field reaches 298.09 V/m and the SAR is 1.14 W/kg, which are both within established safety limits (614 V/m and 2 W/kg per 10 g of tissue). Furthermore, a 5 W, 1 MHz system operating across a 2 mm tissue gap demonstrates power transfer efficiencies of 40.61% for skin tissue and 20.53% for muscle tissue. These results validate the system’s safety and efficiency for powering deeply implanted biomedical devices.